Nonlinear Modeling of Ground Motions at Lotung LSST Site with Nested Surface Soil Constitutive Model. (2nd September 2019) - Spears, Robert; Veeraraghavan, Swetha; Coleman, Justin
Abstract: Seismic analyses of nuclear facilities require the use of validated numerical models that can realistically reproduce the response of soils during earthquakes. The nested surface nonlinear, hysteretic soil constitutive model is one of the soil constitutive models that is widely used because of (1) its lower number of free parameters compared to other nonlinear soil constitutive models and (2) the ease of calibrating these parameters using the commonly available soil data, i.e., G/Gmax and damping curves, as a function of shear strain. This material model is available in the commercial finite element software packages LS-DYNA and Abaqus as well as in the open source finite element tool Mastodon. The purpose of this study is to estimate the parameters required for this material model from the soil data available for the Lotung site and to demonstrate that this nonlinear soil constitutive model used in a time domain, finite element analysis can reasonably reproduce the actual measured soil motions recorded at Lotung during the LSST07 event on May 20, 1986. Results are presented from all the three software packages mentioned above using the same material model.